Student interest and motivation in learning arts and culture using the project-based learning method at State Senior High School 7 Pekanbaru - Kurniati, Fatia; Syefriani, Syefriani (Dewa Ruci: Jurnal Pengkajian dan Penciptaan Seni, 2024)
This study aims to determine the interest and motivation of students in learning arts and culture at State Senior High School 7 Pekanbaru. The research method used is a descriptive quantitative method. The data collection techniques used in the study are documentation, interviews, and the instrument in the form of a questionnaire. The population in this study were students of State Senior High School 7 Pekanbaru, and the research sample was class X students with the material Tanjak Warisan. The method used in learning arts and culture is project-based learning, which involves students designing, planning, and carrying out projects to produce products, publish, or present them. Results show interest and motivation in students at the School State Senior High School 7 Pekanbaru in the sufficient height category. This is based on the results of filling out the interest questionnaire with an average percentage of 81% and an average percentage for the results of the motivation questionnaire of 72%. In addition, in the summative assessment, the average student scored 90. From the interview results, it was found that the students follow a learning art culture. Because, like art lessons, they are enthusiastic about making or producing works of art, are interested in the uniqueness of local and regional arts (local wisdom), and feel comfortable with the way teachers teach in class and the provision of supporting facilities for learning art culture by the school. From the results of this study, there is information explaining that the learning method and teaching variations of teachers are one of the supporters of interest and motivation to learn in students. In addition, this study is expected to provide information on learning methods that educators can use in the classroom and an increase in teachers' awareness of the latest learning methods and teaching variations.